Why is There Zero Women Candidate for Governor Election in West Java, Indonesia? - Malihah, Elly; Nurbayani, Siti; Anggraeni, Leni (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
Democracy requires active public political participation. Sustainability of general elections is vitally important in democracy. As a developing country, Indonesia is still struggling to implement its democracy. Interesting phenomena in Indonesian democracy, the number of women who run their candidacy in an election is still limited. For instance, in West Java Province Regional Election, there are no women candidates for governor or vice governor. The political sociology perspective sees these phenomena as the patriarchal culture that the community prefers male leader to women. This research aimsÃ‚Â atÃ‚Â understandingÃ‚Â causesÃ‚Â of why there are noÃ‚Â femaleÃ‚Â candidatesÃ‚Â in the general election in West Java. This researchÃ‚Â makes use ofÃ‚Â quantitative approach with survey method aimed to explain political viewsÃ‚Â of West Java society about female candidatesÃ‚Â in a gubernatorial election. The area of the researchÃ‚Â coversÃ‚Â West Java province, involving 500 respondents. The data was collected by using the questionnaire distributed by Google Form to people living in this area. The data wereÃ‚Â thenÃ‚Â analyzed by inferential statistics. This studyÃ‚Â indicatesÃ‚Â that West JavaÃ‚Â residentsÃ‚Â stillÃ‚Â holdÃ‚Â strong ideology on gender differences, believing that a good leader should be male. Even in the smallest scope of institution,Ã‚Â menÃ‚Â is suppossedÃ‚Â be a leader. In addition, there is a dichotomy between the public and the personal space for male and female duty. Women are suggested to stay at the private space, while male has a duty at the public sphere. It is alsoÃ‚Â evidencedÃ‚Â in the research that women voters have little tendency to elect the female candidates. ThisÃ‚Â occursÃ‚Â not just because of their patriarchal cultural background, but alsoÃ‚Â due toÃ‚Â their education. ItÃ‚Â isÃ‚Â indicated that evenÃ‚Â femaleÃ‚Â voters had higher education, their tendency to elect the women candidate was still low. Ã‚Â